Gram-Positive Bacteria Are Potent Inducers of Monocytic Interleukin-12 (IL-12) while Gram-Negative Bacteria Preferentially Stimulate IL-10 Production - Hessle, Christina (American Society for Microbiology, 2000)
Interleukin-10 (IL-10) and IL-12 are two cytokines secreted by monocytes/macrophages in response to bacterial products which have largely opposite effects on the immune system. IL-12 activates cytotoxicity and gamma interferon (IFN-γ) secretion by T cells and NK cells, whereas IL-10 inhibits these functions. In the present study, the capacities of gram-positive and gram-negative bacteria to induce IL-10 and IL-12 were compared. Monocytes from blood donors were stimulated with UV-killed bacteria from each of seven gram-positive and seven gram-negative bacterial species representing both aerobic and anaerobic commensals and pathogens. Gram-positive bacteria induced much more IL-12 than did gram-negative bacteria (median, 3,500 versus 120 pg/ml at an optimal dose of 25 bacteria/cell; P < 0.001), whereas gram-negative bacteria preferentially stimulated secretion of IL-10 (650 versus 200 pg/ml; P < 0.001). Gram-positive species also induced stronger major histocompatibility complex class II-restricted IFN-γ production in unfractionated blood mononuclear cells than did gram-negative species (12,000 versus 3,600 pg/ml; P < 0.001). The poor IL-12-inducing capacity of gram-negative bacteria was not remediated by addition of blocking anti-IL-10 antibodies to the cultures. No isolated bacterial component could be identified that mimicked the potent induction of IL-12 by whole gram-positive bacteria, whereas purified LPS induced IL-10. The results suggest that gram-positive bacteria induce a cytokine pattern that promotes Th1 effector functions.